Hoax Dalam Perspektif Hindu - I Komang Mertayasa (Lembaga Penelitian dan Pengabdian pada Masyarakat Institut Agama Hindu Negeri Tampung Penyang Palangka Raya, 2019)
The hoax circulation is very fast because some social media users share without reading or knowing more about whether it's true or not. Increasing literacy can be done well if someone has adequate religious knowledge. The Hinduism have a perspektif the existence of hoax, by understanding it can function as the basis and filter of information to break the chain of hoax circulation. Hoax is made with the aim of making public opinion, herding public opinion, forming perceptions that tests the intelligence and accuracy of internet and social media users. Fake news (hoax) is an act that is not good (asubha karma) so that can be of suffering, therefore in receiving information must maximize wiweka to learn. There are three ways that are used to examine information contained in social media to be able to find out the truth, namely 1). Pratyaksa Pramana; 2). Anumana Pramana; 3). Agama Pramana.